Clinical Evaluation of Autologous and Allogeneic Stem Cell Therapy for Intrauterine Adhesions: A Systematic Review and Meta-Analysis - Chen, Jia-ming; Huang, Qiao-yi; Chen, Wei-hong; Lin, Shu; Shi, Qi-yang (Frontiers in Immunology, 2022)
Abstract Objective: Intrauterine adhesions (IUAs) are a major cause of female infertility. Stem cells can be used to restore endometrial function owing to their regenerative abilities. We compared the safety and efficacy of autologous and allogeneic stem cell treatments in patients with recurrent IUA after conventional therapy based on a systematic review of the related literature. Methods: The PubMed, Embase, and Cochrane databases were systematically searched. All analysis were performed using Review Manager 5.4. We compared improvements in endometrial thickness, pregnancy rates, menstruation, and side effects after autologous and allogeneic stem cell therapy. The study was registered with PROSPERO, CRD 42022322870. Results Our search returned 154 reports, 10 of which met the inclusion criteria, representing 116 patients. Of these, 44 patients in two studies were treated with allogeneic stem cells and 72 patients in eight studies were treated with autologous stem cells. Improvements in endometrial thickness and pregnancy rates after intrauterine device treatment were compared between the autologous and allogeneic stem cell groups. Endometrial thickness increased more after autologous stem cell IUA treatment (mean difference, 1.68; 95% confidence interval [CI]: 1.30–2.07; P < 0.00001), and the pregnancy rate was also improved (relative risk, 1.55; 95% CI: 1.19–2.02, P < 0. 001). No obvious and serious adverse reactions were observed during stem cell therapy in either group. Conclusions: This meta-analysis and systematic review of the results of randomized trials of autologous and allogeneic stem cell treatments for IUA suggests that autologous stem cells have a better effect in improving the endometrium thickness and pregnancy rate.